Ameliorative effects of vitamin C and garlic (Allium sativum) on nifedipine-induced reproductive dysfunction in a male albino rat model - Njoga, Ugochinyere J.; Anya, Kenneth O.; Ekere, Samuel O.; Amune, Faith. N.; Eze, Lawrence U.; Awachie, Mark E.; Ojimba, Loveth C.; Ochiogu, Izuchukwu S.; Njoga, Emmanuel O. (Frontiers in Veterinary Science, 2026)
IntroductionNifedipine, a calcium channel blocker widely prescribed for hypertension, has been implicated in oxidative stress–mediated reproductive toxicity. This study investigated the ameliorative effects of vitamin C and garlic (Allium sativum) on nifedipine-induced reproductive dysfunction in a male albino rat model.MethodsTwenty-five adult male rats were randomized into control and treatment groups, receiving nifedipine (0.571 mg/kg) alone or in combination with vitamin C (200 mg/kg) and/or garlic extract (200 mg/kg) for 40 days. Reproductive parameters and histopathological changes in the testes and epididymis were assessed.ResultsNifedipine administration significantly reduced sperm parameters compared to control-sperm motility (38.9 ± 2.53 vs. 83.25 ± 1.65 in controls, P ≤ 0.05), viability (88.03 ± 1.87 vs. 94.00 ± 0.98), and normal morphology (80.75 ± 0.85 vs. 89.5 ± 0.65), while co-administration of vitamin C and vitamin C + garlic combination slightly mitigated these effects, improving sperm motility to 41.25 ± 6.95 and 45.00 ± 7.5, respectively. The combined treatment produced the most profound improvement, restoring sperm motility (6.1 % increase), viability (3.15 % increase, close to control values), and normal sperm (4% ameliorative effect, P ≤ 0.05). Histopathological analysis revealed substantial preservation of testicular and epididymal integrity in the vitamin C and less in the combination (vitamin C + garlic) and garlic treatment groups.ConclusionNifedipine caused significant impairments in sperm quality and histological integrity. Vitamin C and garlic combination produced a statistically significant improvement in normal sperm morphology, with other parameters showing non-significant numerical increases. Further research with larger sample sizes and biochemical analyses is needed to clarify the extent of antioxidant influence on nifedipine-induced reproductive alterations.